Hypothalamic Subependymal Niche: A Novel Site of the Adult Neurogenesis - Rojczyk-Gołębiewska, Ewa (Springer US, 2014)
The discovery of undifferentiated, actively proliferating neural stem cells (NSCs) in the mature brain opened a brand new chapter in the contemporary neuroscience. Adult neurogenesis appears to occur in specific brain regions (including hypothalamus) throughout vertebrates’ life, being considered an important player in the processes of memory, learning, and neural plasticity. In the adult mammalian brain, NSCs are located mainly in the subgranular zone (SGZ) of the hippocampal dentate gyrus and in the subventricular zone (SVZ) of the lateral ventricle ependymal wall. Besides these classical regions, hypothalamic neurogenesis occurring mainly along and beneath the third ventricle wall seems to be especially well documented. Neurogenic zones in SGZ, SVZ, and in the hypothalamus share some particular common features like similar cellular cytoarchitecture, vascularization pattern, and extracellular matrix properties. Hypothalamic neurogenic niche is formed mainly by four special types of radial glia-like tanycytes. They are characterized by distinct expression of some neural progenitor and stem cell markers. Moreover, there are numerous suggestions that newborn hypothalamic neurons have a significant ability to integrate into the local neural pathways and to play important physiological roles, especially in the energy balance regulation. Newly formed neurons in the hypothalamus can synthesize and release food intake regulating neuropeptides and they are sensitive to the leptin. On the other hand, high-fat diet positively influences hypothalamic neurogenesis in rodents. The nature of this intriguing new site of adult neurogenesis is still so far poorly studied and requires further investigations.